IN VITRO ADME STUDIES OF TUG-891, A GPR-120 INHIBITOR USING SWISS ADME PREDICTOR - Mishra, Shweta; Dahima, Rashmi (Journal of Drug Delivery and Therapeutics, 2019)
Predicting the absorption, distribution, metabolism and elimination (ADME) profile of drug candidates before their synthesis, in the early stage of drug discovery, could help in selecting candidates with the less critical ADME profile. In vivo ADME assessment is found to be costly, time consuming and involve the lives of animals, so the in vitro ADME analysis is better, cheaper and provides accurate results quickly. TUG-891 is a GPR-120 inhibitor under clinical trials. The aim of the present study is to predict the in vitro ADME studies of TUG-891, to know the expected outcome of the clinical trials and finding the correlation between the in vivo and in vitro results along with the improvisation in the structure of the TUG-891, so that the biological activity remains unaffected, but reduces the unwanted ADME effects. The 2D and 3D structures of TUG-891 were drawn on chemdraw 3D-Ultra version 8.0 by minimizing the energy using MM2 and MOPAC setting the minimum RMS gradient to 0.01. The structure was imported, the structure smiley was entered and the Swiss ADME drug design study was run. The bioavailability radar showed that the colored zone is the suitable physicochemical space for oral bioavailability where the following properties were taken into consideration as flexibility, lipophilicity, saturation, size, polarity and solubility. The pharmacokinetic properties were studied using the boiled egg model allows for intuitive evaluation of passive gastrointestinal absorption and brain penetration in function of the position of the molecules in the WLOGP-versus-TPSA referential. The white region is for high probability of passive absorption by the gastrointestinal tract and the yellow region that is yolk, is for high probability of brain penetration. Yolk and white areas are not mutually exclusive. Through the study conducted it could be concluded that the aqueous solubility of the compound should be increased along with the fraction of sp3 hybridized carbon atoms. The molecule should not be the inhibitor of metabolizing enzymes and so further modifications need to be done on the lead structure.